2020
DOI: 10.3389/fphys.2020.00800
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Study of Fetal Membrane: Inflammation-Triggered Proteolysis of Extracellular Matrix May Present a Pathogenic Pathway for Spontaneous Preterm Birth

Abstract: Introduction: Spontaneous preterm birth (sPTB), which predominantly presents as spontaneous preterm labor (sPTL) or prelabor premature rupture of membranes (PPROM), is a syndrome that accounts for 5-10% of live births annually. The longterm morbidity in surviving preterm infants is significantly higher than that in full-term neonates. The causes of sPTB are complex and not fully understood. Human placenta, the maternal and fetal interface, is an environmental core of fetal intrauterine life, mediates fetal oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 63 publications
2
15
1
Order By: Relevance
“…This was in consistent with a previous study that mRNA levels of CXCL9, CXCL10, and CXCL11 in the FMs of patients with chronic chorioamnionitis were higher than the control group [51]. And ICAM-1 was over-expressed in FMs from women with PL than TL by proteomic analysis [52]. Besides, it was identified that these chemokines released from FMs could recruit immune cells [31].…”
Section: Discussionsupporting
confidence: 91%
“…This was in consistent with a previous study that mRNA levels of CXCL9, CXCL10, and CXCL11 in the FMs of patients with chronic chorioamnionitis were higher than the control group [51]. And ICAM-1 was over-expressed in FMs from women with PL than TL by proteomic analysis [52]. Besides, it was identified that these chemokines released from FMs could recruit immune cells [31].…”
Section: Discussionsupporting
confidence: 91%
“…HSPH1 has been found to be associated with proteolysis in differentiated neurons ( Deane and Brown, 2017 ). EPHB2 ( Ibrahim et al, 2018 ; Pan et al, 2020 ) TNF-α/nuclear factor-kappa B signaling has been reported to worsen cognitive impairment ( Tang et al, 2019 ). PDGFA is important for the growth and maintenance of the nervous system ( Cardona et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A proteomic study of fetal membrane between preterm and full-TL revealed 62 proteins differentially expressed, which were involved in inflammation, T cell/macrophage activation, metabolism and synthesis, cell adhesion, proteolysis, and extracellular matrix pathways. 84 As an important barrier between fetus and mother, cortisol degradation and regeneration in the fetal membranes is a requisite event in parturition. 90 Cortisol involves in the rupture of fetal membranes through decreasing collagen I, III, IV, or inducing serum amyloid A1 to remodel extracellular matrix.…”
Section: Fetal Membranementioning
confidence: 99%
“…83 Placenta RNA-seq and metabolomics studies suggest that placenta mitochondrial function and energy metabolism are altered, and the imbalanced glycolysis and unconventional lactate oxidation may be associated with sPTL. 84,85 The placenta-derived extracellular vesicles proteins proteome revealed that nonspecific inflammation coagulation was upregulated while complement activation-related proteins were downregulated in cargo from first trimester in sPTL. 86 These differentially expressed molecules in placenta exerted different roles in the occurrence of sPTL.…”
Section: Placentamentioning
confidence: 99%